2023
DOI: 10.1002/nse2.20104
|View full text |Cite
|
Sign up to set email alerts
|

Jumble judging: Cognitive and affective outcomes of intercollegiate collaboration at a soil judging competition

Abstract: Student-student interactions are influential parts of field experiences. While competitive judging events are a fun way to engage students in field-based learning, the focus on competition leads to an atmosphere that discourages collaboration between students. The objective of this study was to evaluate the cognitive and affectiveThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Studies have documented several benefits of hands-on and co-operative learning activities like soil judging contests. For example, soil judging contests motivate a student's learning process by working independently and collaboratively as a team with other students, promote student engagement due to coach-student interactions, and help explore, describe, and interpret soils in their in-situ state [2,5,6]. Rees & Johnson [4] (2020) reported that in-person soil judging contests help students understand locationspecific soils and develop positive attitudes toward soil science.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have documented several benefits of hands-on and co-operative learning activities like soil judging contests. For example, soil judging contests motivate a student's learning process by working independently and collaboratively as a team with other students, promote student engagement due to coach-student interactions, and help explore, describe, and interpret soils in their in-situ state [2,5,6]. Rees & Johnson [4] (2020) reported that in-person soil judging contests help students understand locationspecific soils and develop positive attitudes toward soil science.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the team judging part of the soil judging contest and the opportunity to interact with other students and coaches from different universities can create a co-operative learning environment, which can help students to learn, and problem solve in real-time through working with their peers, improve their communication skills, and prepare students to work as a team member [8]. In essence, soil judging contests allow students to learn about various soil types in a given region and interact with students and peers from their university and other participating schools [3,5,6]. The framework of the SSSA-ASA regional and national contests is the same, but the format of individual soil judging contests may differ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations